Ioannis Kolettis. The Vlach from the ruling elite of Greece - Jovanovski, Dalibor; Minov, Nikola (Balcanica Posnaniensia. Acta et studia, 2018)
The purpose of this article is to show how Ioannis Kolettis, the first Vlach to become Prime Minister of the Kingdom of Greece, governed Greece, and why he is remembered, even today, as one of the Prime Ministers who left a lasting impression on Greek internal politics, and, especially, on Greek foreign affairs.